Short-term open innovation hackathons as a method to improve tourism innovation. - Cerdeña, Lucía Santana; Rivero, Jose P. Suárez (The journal of contemporary issues in business and government, 2021)
This article has as objective the use case study applied by Lopesan Hotel Group, the Hackathon Think in Innovation; whose goal was to promote Open Innovation in the hotel group, providing solutions to the challenges identified by the organization and promoting the creation of an innovative culture within the company. The evaluation results of the participants during two editions (years 2015 and 2016) are analyzed, amounting to a total of 94 surveys. Likewise, the benefits and the reasons why the format have not been continued by the hotel group are exposed. In general, the format has given Lopesan Hotel Group recognition as an innovative brand, generating a rich source of future projects to develop internally or externally.